Recapitalization and Banks Performance in Ghana - Alnaa , Samuel Erasmus; Ahiakpor , Ferdinand; Abdul-Majeed, Ahmed (Asian Journal of Empirical Research, 2020)
This study seeks to examine the profitability performance of local banks during the pre and post recapitalization period. Using the data of domestic banks from 2006 to 2016, and based on descriptive statistics, ratio analysis, and t-test, the study reveals that recapitalization policy has a positive effect on management efficiency for Ghana Commercial Bank. Management efficiency was 67.80 and 68.27 for pre and post recapitalization respectfully. However, CAL bank and HFC performed poorly in management efficiency after the recapitalization exercise. Again, the study reveals that CAL bank and HFC also performed better in Return on Assets after recapitalization. Finally, the study further shows a low rate of returns on shareholders’ dividend, Return on Equity, after the recapitalization. From the findings, we conclude that recapitalization had negative effects on the performance of the local banks in Ghana. Therefore, we recommend, among other measures, that banks should endeavour to sustain their management efficiency, which translates into a positive total asset turnover. Also, the management of banks should manage their equity capital raised from shareholders very well to generate enough earnings for these shareholders, as this will entice other investors into the banking industry.